Legal Consequences of Downstreaming in The Mineral and Coal Mining Business - Yapiter Marpi (International Journal of Qualitative Research, 2021)
This paper aims to analyze the consequences of commodity dependence, an impact on the trend of natural resources exported in raw form. On the one hand, it creates a loss factor in the loss of value opportunities in the acquisition of added value for the Indonesian state, and then it also creates too many opportunities for foreign parties in obtaining industrial raw materials. Precisely due to the liberalization of mineral exploitation and exploitation of foreign parties, many leave big social and environmental problems. The research method in this paper uses a normative legal approach supported by socio-legal, qualitative analysis of social and environmental norms. The research results are papers on the effectiveness of the downstream process so that it has resistance to the dynamics of the trade economy and global conditions. So that in the future independently to process mineral and coal natural resources and optimize the latest mineral and coal regulations and provide facilities for various Omnibuslaw management permits to create a centralized policy system and use of raw materials for domestic industries to achieve results to encourage commodity-based regional economies to influence economic growth independent which guarantees and provides benefits for the welfare of the people.